Influence of Weave into Slippage of Yarns in Woven Fabric - Edita MALČIAUSKIENĖ; Algirdas MILAŠIUS; Ginta LAURECKIENĖ; Rimvydas MILAŠIUS (Medžiagotyra, 2011)
Slippage resistance of yarns at a seam in woven fabrics is a very important factor and very strict claims are raised for this property. It is necessary to know how fabric structure influences on seam slippage quality before manufacturing the fabric. The purpose of this work was to establish which of the weave factor is most suitable to describe balanced weave fabrics seam slippage. It was investigated seam slippage characteristics in the fabric and the factor was offered, which characterizes best fabric structure from the thread slippage point of view. Fifteen wool fabrics, which differ only on weave were weaved for investigations. The test was carried out according to LST EN ISO 13936-1standard. First of all, the well known factors such as fabric structure factor P and average float F were investigated and then a new fabric structure factor was offered, which the best characterizes the weave from thread slippage point of view. The proposed model shows good correlation between experimental and theoretical values of the new weave factor. http://dx.doi.org/10.5755/j01.ms.17.1.248